Effects of Posttreatments on the Storage Stability of Reclaimed Rubber - Na Lu; Mei Shen; Juan Liu; K. Prakashan; Zhenxiang Xin (Advances in Polymer Technology)
Reclaimed rubber should be considered a source of new material with an economic impact, so the recycling of waste rubber is especially important. In this paper, sulfur-cured waste tire rubber powder is successfully devulcanized in a normal-pressure continuous regeneration system under the application of an activator and aromatic oil. Then, the reclaimed rubber was subjected to further mechanical shearing using a two-roll mill, rubber extruder, and rubber strainer. The effects of the storage time at room temperature on the properties and structure of reclaimed rubber were examined by sol fraction measurement, Mooney viscosity measurement, crosslink density measurement, tensile property testing, and Rubber Process Analyzer (RPA) measurement. The results under the test conditions indicated that different postprocessing operations were not making much difference to the properties of the reclaimed rubber. But the effect of storage time is more significant; the Mooney viscosity value increased from 65 to 90 when the storage period increases to 60 days, the sol fraction decreased, and the crosslink and density storage modulus also increased with increasing storage time due to the slow recombination and aggregation of the molecular fragments with free radicals happening in the reclaimed rubber during the storage.